Enhancing Inclusion within Responsible Innovation Process through Serious Gaming - Szatkowska, Weronika Zuzanna (Media - Culture - Social Communication, 2021)
This paper presents a theoretical consideration of the use of serious games to enhance inclusiveness in the process of creating so-called responsible innovation. The literature regarding the impact of serious games on inclusion with its possible implications for a responsible innovation process is explored. The article sheds light on the concept of serious gaming, including its aims, core elements and the learning process. It tackles inclusion within different contexts and its origins, linking it to gaming. The responsible innovation concept is explained from this perspective, with attention paid to inclusion. Next, a systematic literature review is presented, focusing on recent sources fromthe JSTOR database. It is followed by selected cases of games enhancing inclusion. The article summarizes the outcomes of the review and compares them with the theoretical assumptions. In the conclusion, the topic of using serious games as a promising method to improve the level of inclusiveness in the process of creating responsible innovations is addressed. It was also noted that, from the point of view of the creators of responsible innovations, particularly interesting areas are studies devoted to urban and environmental issues, as well as articles on natural sciences, technology, engineering and mathematics.